E2: Equity and Excellence Framework - Adrienne Coleman; Traci Ellis (Athens Institute for Education and Research, 2023)
Both the United States and the United Nations have identified, examined, and put out a call to action to address the educational inequities that have disproportionately and negatively affected racially minoritized students, as well as those from a lower socioeconomic background, and poorer countries. Data from the Nations Report Card and the Global Monitoring Report provide evidence of disparities in academic performance and access to equitable educational resources. The outcome of these inequities impacts countries throughout the world, as their residents will not possess the skills and knowledge to thrive in a rapidly evolving global society, nor possess the critical thinking and analytical skills to solve the problems of the world. Considering there is a national and global equity focus, the Illinois Mathematics and Science Academy engaged in a process of participatory action research to institutionalize and operationalize equity and excellence, ultimately addressing educational inequities. This resulted in the development of the E2: Equity and Excellence Framework, inclusive of the following equity pathway steps: Educational Equity Impact Case, Equity and Excellence Policy, Equity-mindedness Capacity Building, Equity-mindedness Data Collection, Equity-mindedness Meaning-Making, Equity and Excellence Plan, and Equity Scorecard. This framework is a comprehensive, research-informed, equity-minded, inclusive pathway towards advancing educational equity that centers the voices of those with the most risk of experiencing inequities. Educational institutions that want to confront, diminish, and potentially eliminate educational inequities can apply this scalable and adaptable framework.